The Utilization of Tuna (Yellowfin tuna), Sweet Potato (Ipomoea batatas) and Sago (Metroxylon sago sp) in making of Kamaboko - harijono, Harijono; yunianta, Yunianta; Suryono, M. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
Kamaboko is a traditional Japanese food products from the results of fish flesh process which gel form, that is spatially springy and elastic. The supply scarcity of alaska pollock raw materials and itâ€™s price rise make tuna fish (Yellowfin tuna) utilization which is overflows and cheap regard as an alternative. In addition, the sweet potato and sago which the utility as a filler of kamaboko are also abundant in Papua and it will also support the local. This research aims to determine the influence of treatment of different concentrations of sweet potato and sago flour accordingly in making of kamaboko.This research were using random group design with one factor of different treatment concentration of flour sweet potato and sago (K), namely K1 = sweet potato 0%: sago 10%, K2 = sweet potato 2%: sago 8%, K3 = sweet potato 4%: sago 6%, K4 = sweet potato 6%: sago 4%, K5 = sweet potato 8%: sago 2%, and K6 = sweet potato 10%: sago 0% towards the concentration of tuna fish 90%. The influence of treatment carried out measurements on 3 variables: chemistry value i.e. the levels of protein, fat, water, and carbohydrates; the physics value i.e. parameters of Â Water Holding Capacity (WHC), texture, broken power and color; organoleptic value i.e. taste, texture, aroma, compactness, colours and elasticity that indicate K4 is the best treatment. The value chemical of K4 treatment indicate that levels of protein 19.40%, fat 0.19%, water 69.82%, and carbohydrates 6.08%; the physics value i.e. parameters of WHC 43.61%, texture 11.93 N, broken power 7.83N/m, color brightness (L*) 50.31, redness (a*) 14.14, yellowness (b*) 14.13; organoleptic value i.e taste, compactness, color, and elasticity, K4 treatment slightly favored with the texture and aroma is neutral. Keywords: Kamaboko, sweet potato, sago, tuna fish, formulation, texture